Epidemiology and Molecular Characterization of Clostridium difficile Strains from Patients with Diarrhea: Low Disease Incidence and Evidence of Limited Cross-Infection in a Swedish Teaching Hospital - Svenungsson, Bo (American Society for Microbiology, 2003)
We prospectively studied the epidemiology of Clostridium difficile-associated diarrhea (CDAD) in a 900-bed hospital over the course of 12 months by PCR-ribotyping of C. difficile isolates. A total of 304 cases were diagnosed, corresponding to an overall incidence of 7/1,000 admissions, with higher rates in nephrology, hematology, and organ transplantation wards (37, 30, and 21/1,000), and 72% were classified as hospital associated (onset in hospital or onset at home but after a hospital stay within 2 months). All 382 isolates from 227 of 304 (75%) patients available for PCR-ribotyping were typeable, yielding 70 PCR-ribotypes. The three most common types comprised 30% of hospital-associated and 34% of community-associated cases, indicating import via admitted patients as a major source of C. difficile strains occurring in the hospital. Of the 227 patients studied, 38% each contributed 2 to 13 fecal samples positive for C. difficile over the course of the study period. Repeat isolates of the same PCR-ribotype as the first isolate were found in 79% of these patients and in 95% of specimens delivered within 30 days, compared to 63% of those obtained at 31 to 204 days. Nosocomial acquisition of CDAD, defined as the proportion of cases sharing C. difficile type and admitted to the same ward within 2 or 12 months, was 20% and 32% of hospital-associated cases and 14% and 23% of all cases, respectively. Thus, most CDAD cases diagnosed over the course of the study period, including those associated with hospitalization, appeared to be caused by endogenous C. difficile strains rather than by strains truly being acquired in the hospital.